Effect of solvent/additives ratio on cellulose acetate dialysis membrane formation and urea clearance - Idris, Ani (2005)
Cellulose acetate flat sheet asymmetric dialysis membranes were fabricated via phase inversion process using acetic acid as the solvent. The effects of solvent to polymeric additives (polyethylene glycol; PEG 600) ratio on the morphology and urea clearance of the dialysis membranes were investigated. Dialysis membranes from six different formulations were tasted using phase inversion method and were tested using single layer dialysis apparatus. The performances of the obtained membranes were tested using 1 mg/mL urea solution and the morphology of the membranes was characterized using scanning electron microscope. It was found that higher acetic acid/PEG ratio provide better urea clearance performance. Furthermore, the amount of additives strongly affects the membrane structure. Higher acetic acid/PEG ratio induced the formation of finger like structure macrovoids whilst dense spongy structures were found with lower acetic acid/PEG ratios. However, control experiment showed that the presence of PEG in the dope formulations is essential in order to increase the dialysis membrane performance.